Challenges of the Fast Food Industry in India : An Integrated ISM-MICMAC Approach - Hota, Jyotiranjan; Tripathy, Arvind; Deb, Mahuya (Indian Journal of Marketing, 2023)
Purpose : India's fast food industry was the fastest-growing in the last decade, but not everything was as shiny as it looked from the outside. Many challenges were posing a threat to the survival of this industry. So, the purpose of the present study was to conduct a structural analysis of the challenges of the fast food industry in India using interpretive structural modeling (ISM). Design/Methodology/Approach : Challenges of fast food industries have been identified from the literature, which was further endorsed for significance using responses from the domain experts through a structured questionnaire. The rationale of this paper was to apply ISM to develop a hierarchical structure among the vital challenges of fast food industries in India. The ISM technique analyzed the mutual interaction and ranking among the challenges. Furthermore, MICMAC analysis was applied to explain this dependence and driving power challenges. Findings : During the first phase of the research, an opinion survey of experts was endorsed. The challenges of â€œlack of fresh ingredientsâ€ and â€œavailability of ready-to-eat mealsâ€ were dropped based on the t-test. ISM was applied to the validated challenges. Ten validated challenges were modeled into five levels. â€œChanging tastes of millennial customersâ€ was found to be the most important challenge of the fast food industry, which appeared at the lowest level. The ISM model supported examining and building up a model of interactions, mutual influence, and relationships among the challenges faced by the fast food industry. Limitations : The research work bounded the study in India, and subjectivity in expert opinion might exist. Practical Implications : The study is relevant to fast food industry professionals, food delivery aggregators, and food processing and packaging professionals. They need to be aware of the lacunae, the importance of challenges, and their interdependence found out from the study for future courses of action. Originality/Value : The study investigated the core challenges of the fast food industry in India. Secondly, it had methodological novelty in the context. Finally, the study led to a multidimensional implication for various stakeholders in India's fast food industry context.